Workshop on scenario-guided policy analysis for development, food security and environment in the Andean region - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Regional stakeholders from governments, development organizations and academia came together from 12 to 14 November in Lima, Peru for a workshop that focused on scenario-guided policy analysis on the future of development, food security and the environment under climate change in the Andean region. The workshop was organized by UNEP-WCMC in collaboration with CCAFS and is part of UNEP-WCMC’s project Commodities and Biodiversity, Planning for Future Capacity funded by The MacArthur Foundation. Photos: E. van de Grift.